PENGARUH CYBER LAW TERHADAP KEPERCAYAAN MASYARAKAT DALAM LAYANAN ONLINE - Wisnu Cahyo Apriliyadi; Pandri Zulfikar; Muhammad Fajar Alfahimi; Aditya Putra Setyawan; Ahiruddin (CV. Lafadz Jaya, 2026)
The development of information and communication technology has transformed the paradigm of social and economic interaction through online services. However, the proliferation of cybercrime, personal data breaches, digital fraud, and illegal content has threatened public trust in the digital ecosystem. Cyber Law as a legal instrument governing cyberspace is expected to build and maintain public trust. This study analyzes the influence of Cyber Law on public trust in using online services through a normative juridical and empirical socio-legal approach. The results show that the effectiveness of Cyber Law in building trust depends on several factors: regulatory clarity, consistency of law enforcement, public legal awareness, and balance between protection and innovation. This study recommends regulatory harmonization, strengthening of cyber law enforcement institutions, and development of alternative dispute resolution mechanisms to increase public trust in online services.